2020
DOI: 10.21037/apm-20-886
|View full text |Cite
|
Sign up to set email alerts
|

A novel nomogram based on SEER database for the prediction of liver metastasis in patients with small-cell lung cancer

Abstract: Background: To establish and validate a nomogram to predict liver metastasis in patients with small-cell lung cancer (SCLC).Methods: Information on patients diagnosed with SCLC between 2010 and 2015 was retrospectively retrieved from the Surveillance, Epidemiology, and End Results (SEER) database. Risk factors for liver metastasis were identified by logistic regression analyses to construct a nomogram. The predictive accuracy was evaluated by concordance indexes (c-index) and calibration plots, and the compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…While nomogram can be used to estimate the distantmetastasis risk by integrating the existing clinicopathological factors, improving diagnostic efficiency, reducing time, and economic cost. [ 21 , 22 ] So it is necessary to establish a simple and sensitive prediction model for distant metastasis in MBC patients. The study established a risk prediction model based on the existing evidence to assess the risk of distant metastasis and screen high-risk groups, so as to guide diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While nomogram can be used to estimate the distantmetastasis risk by integrating the existing clinicopathological factors, improving diagnostic efficiency, reducing time, and economic cost. [ 21 , 22 ] So it is necessary to establish a simple and sensitive prediction model for distant metastasis in MBC patients. The study established a risk prediction model based on the existing evidence to assess the risk of distant metastasis and screen high-risk groups, so as to guide diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with single-site metastases from NSCLC, liver metastases have a relatively shorter median survival compared to brain or bone metastases. Patients with multisite metastases had a worse prognosis than single-site metastases, and among patients with multisite metastases, OS was reduced by 1 month or more in patients with liver metastases than in patients without liver metastases 17 .…”
Section: Discussionmentioning
confidence: 89%
“…Leyrer CM et al reported only 41% (46/113) patients were identified preoperatively as MBC on initial image-guided core biopsy [ 31 ]. Furthermore, nomogram, as a simple and advanced prediction tool, can estimate individualized risk by integrating substantial clinicopathological characteristics [ 39 ]. Therefore, it is necessary to establish a simple and sensitive preoperative prediction model of regional LNM in MBC patients.…”
Section: Discussionmentioning
confidence: 99%